Scarlet-bodied wasp moth, Cosmosoma myrodora (Dyar) (Insecta: Lepidoptera: Arctiidae) - Diego Moscoso; Rodrigo Diaz; William A. Overholt (EDIS)
The scarlet-bodied wasp moth, Cosmosoma myrodora (Dyar), is a beautiful native insect. Because of its striking adult coloration, including a bright red thorax and abdomen, and transparent wings patterned with black, this moth immediately stands out in Florida landscapes. Larval feeding is restricted to two native plants in the genus Mikania, family Asteraceae. This 5-page fact sheet was written by Diego Moscoso, Rodrigo Diaz, and William A. Overholt, and published by the UF Department of Entomology and Nematology, May 2013.